1996
DOI: 10.1088/0953-8984/8/36/021
|View full text |Cite
|
Sign up to set email alerts
|

Study of intrinsic point defects in oxides of the perovskite family: I. Theory

Abstract: Special features of atomic vacancies in oxides of the perovskite family have been studied within the framework of the Green function method. It has been shown that, in accordance with experiments, the oxygen vacancy has both shallow and comparatively deep levels corresponding to different charge states. The single-charged oxygen vacancy has a deep level and, hence, it could be a good trap for electrons. We shall show that, owing to interaction with the lattice polarization, an electron is captured by one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
30
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 29 publications
8
30
0
Order By: Relevance
“…These Nb atoms remain to be identical; i.e., we did not see formation of dipole moments of the Nb 1 -V O -Nb 2 type, as suggested in Ref. 25. Note that the relevant relaxation energy is several eV which is typical for many point defects in ionic and partly ionic solids.…”
Section: Discussionsupporting
confidence: 71%
“…These Nb atoms remain to be identical; i.e., we did not see formation of dipole moments of the Nb 1 -V O -Nb 2 type, as suggested in Ref. 25. Note that the relevant relaxation energy is several eV which is typical for many point defects in ionic and partly ionic solids.…”
Section: Discussionsupporting
confidence: 71%
“…Hence, a greater number of oxygen vacancies correspond to the generation of more free electrons in CCTO ceramics. Prosandeyev et al [29] reported that ceramics become more conductive as the sintering temperature increases. Since CCTO can be regarded as a Cu-substituted CTO, the grains should become more semi-conducting as the sintering temperature increases.…”
Section: Resultsmentioning
confidence: 99%
“…First, due to the lowering of the local point symmetry at the O site in ferroelectric phases of KNbO 3 (for instance, in the orthorhombic phase which is the room-temperature one), the degeneracy of the 2p-type excited state may be lifted, resulting in several splitted absorption bands. Second, there were claims in the literature in favor of the symmetry breaking between two Nb atoms neighboring the O vacancy, resulting in an asymmetric electron density distribution [6]. In order to clarify these questions and to check the assignment of the 2.7 eV absorption band, we study in the present paper the F center in KNbO 3 using the supercell model and two different theoretical techniques: the full-potential linear muffin-tin orbital (FP-LMTO) and the semiempirical Intermediate Neglect of the Differential Overlap (INDO) methods.…”
Section: Introductionmentioning
confidence: 99%